2005
DOI: 10.1038/sj.jcbfm.9600190
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effects of Virally Delivered HSPs in Experimental Stroke

Abstract: Heat shock proteins (HSPs) are molecular chaperones with essential roles in modulating the proteolytic machinery and accelerating cell repair. Heat shock protein overexpression has been observed in vivo and in vitro under stresses including heat, nutrient deprivation and ischemia. Experiments in in vivo models of stroke indicate that transgenically overexpressed or virally delivered HSPs can enhance cell survival, but cannot always reduce lesion size. This study aims to assess the effects of virally delivered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 83 publications
2
54
0
Order By: Relevance
“…In this context, we have previously shown that in vitro transduction of NPCs with TAT-Bcl-x L is efficient and results in sustained neuroprotection against stroke after intracerebral transplantation of TAT-Bcl-x L -transduced NPCs [19]. Although Hsp70-induced neuroprotection has been shown before [10,[52][53][54], this study shows for the first time that the fusion protein TAT-Hsp70 enhances resistance of NPCs against hypoxic-hypoglycemic injury. Since neuroprotection by the TAT domain itself has been described in vitro recently [55,56], we used TAT-HA as a negative control in order to exclude effects of the TAT domain itself on cell viability, neurosphere formation rates, NPC numbers, and differentiation patterns of NPCs.…”
Section: Discussionmentioning
confidence: 88%
“…In this context, we have previously shown that in vitro transduction of NPCs with TAT-Bcl-x L is efficient and results in sustained neuroprotection against stroke after intracerebral transplantation of TAT-Bcl-x L -transduced NPCs [19]. Although Hsp70-induced neuroprotection has been shown before [10,[52][53][54], this study shows for the first time that the fusion protein TAT-Hsp70 enhances resistance of NPCs against hypoxic-hypoglycemic injury. Since neuroprotection by the TAT domain itself has been described in vitro recently [55,56], we used TAT-HA as a negative control in order to exclude effects of the TAT domain itself on cell viability, neurosphere formation rates, NPC numbers, and differentiation patterns of NPCs.…”
Section: Discussionmentioning
confidence: 88%
“…For example, HSP27 can inhibit apoptosis by reducing caspase activity (33), decrease cytochrome c release from mitochondria (34), and/or inactivate the apoptosis signal-regulating kinase 1/JNK prodeath signaling cascade (17). A number of previous studies reported the neuroprotective effects of HSP27 against cerebral I/R injury when globally expressed in the brain (15)(16)(17)22). However, the anti-cell death properties of HSP27 are unlikely to directly contribute to protection against BBB leakage 1-3 h after I/R, because cell death is not apparent until some hours after this early stage in postischemic ECs (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Under physiological conditions, the level of HSP27 is extremely low in the brain; however, HSP27 expression is transiently induced in brain glial cells and/or ECs at 24 h or later following cerebral I/R (14). Previous studies by our and other groups demonstrated robust neuroprotective effects of HSP27 overexpression against I/R brain injury (15)(16)(17)(18), which were largely credited to its antiapoptotic actions. However, HSP27 exerts additional actions on ECs (14).…”
mentioning
confidence: 95%
“…Although beneficial effects of Hsp70 in experimental stroke have been shown before, these studies were often restricted to models using transgenic Hsp70-overexpressing mice or viral vectors, [6][7][8] making Hsp70 not attractive for clinical application under these conditions. As proteins like Hsp70 do not pass the intact cell membrane or blood-brain barrier (BBB), we have previously fused Hsp70 to the transactivator of transcription (TAT) domain of the human immunodeficiency virus.…”
Section: Introductionmentioning
confidence: 99%